STUDY OF WORKING OF PIPE IN CORAL FOUNDATION - Luong, Hoang Xuan; Dat, Pham Tien; Chung, Nguyen Thai; Tan, Le (Vietnam Journal of Marine Science and Technology, 2007)
In this paper, the authors present some results in the research of interaction between the pipe and the coral foundation of Truong Sa Archipelago by finite element method using slip elements. By using the slip de ments to bring essence true of coral foundation. The results can be used in design as reference for constructions on the coral foundation.